A pangenome analysis reveals the center of origin and evolutionary history of Phytophthora infestans and 1c clade species - Allison L. Coomber; Amanda C. Saville; Ignazio Carbone; Michael Martin; Vanessa C. Bieker; Jean Beagle Ristaino (PLoS ONE, 2025)
We examined the evolutionary history of Phytophthora infestans and its close relatives in the 1c clade. We used whole genome sequence data from 69 isolates of Phytophthora species in the 1c clade and conducted a range of genomic analyses including nucleotide diversity evaluation, maximum likelihood trees, network assessment, time to most recent common ancestor and migration analysis. We consistently identified distinct and later divergence of the two Mexican Phytophthora species, P. mirabilis and P. ipomoeae, from P. infestans and other 1c clade species. Phytophthora infestans exhibited more recent divergence from other 1c clade species of Phytophthora from South America, P. andina and P. betacei. Speciation in the 1c clade and evolution of P. infestans occurred in the Andes. P. andina–P. betacei–P. infestans formed a species complex with indistinct species boundaries, hybridizations between the species, and short times to common ancestry. Furthermore, the distinction between modern Mexican and South American P. infestans proved less discrete, suggesting gene flow between populations over time. Admixture analysis indicated a complex relationship among these populations, hinting at potential gene flow across these regions. Historic P. infestans, collected from 1845–1889, were the first to diverge from all other P. infestans populations. Modern South American populations diverged next followed by Mexican populations which showed later ancestry. Both populations were derived from historic P. infestans. Based on the time of divergence of P. infestans from its closest relatives, P. andina and P. betacei in the Andean region, we consider the Andes to be the center of origin of P. infestans, with modern globalization contributing to admixture between P. infestans populations today from Mexico, the Andes and Europe.